2007
DOI: 10.1097/jcp.0b013e31815ac4d2
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Outcome in Relation to Maternal Use of Some Recently Introduced Antidepressants

Abstract: Little is known concerning possible hazards of maternal use of the recently introduced antidepressant drugs with noradrenergic and varying serotonergic activity (serotonin-noradrenaline reuptake inhibitor [SNRI]/noradrenergic reuptake inhibitor [NRI] drugs). Using the Swedish Medical Birth Registry, we identified 732 women who had used SNRI/NRI drugs in early pregnancy. Maternal characteristics were studied as well as delivery outcome: pregnancy duration, birth weight, neonatal diagnoses, infant deaths, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
102
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 11 publications
13
102
3
3
Order By: Relevance
“…56 Two studies of venlafaxine (with 732 and 150 patients) observed no increased risk of birth defects. 57,58 If medication is needed during pregnancy, preconception planning is ideal. Folic acid supplementation is recommended before conception and during pregnancy for mothers using certain antiepileptics (eg, carbamazepine) to decrease the risk of neural tube defects.…”
Section: Pharmacotherapy For Np During Pregnancy and Breastfeedingmentioning
confidence: 99%
“…56 Two studies of venlafaxine (with 732 and 150 patients) observed no increased risk of birth defects. 57,58 If medication is needed during pregnancy, preconception planning is ideal. Folic acid supplementation is recommended before conception and during pregnancy for mothers using certain antiepileptics (eg, carbamazepine) to decrease the risk of neural tube defects.…”
Section: Pharmacotherapy For Np During Pregnancy and Breastfeedingmentioning
confidence: 99%
“…With respect to the recently introduced antidepressants like SNRIs, several published studies found similar outcomes to those described with the use of other antidepressant categories 3, 10, 11, 12. However, it has been pointed that only a severe teratogenic effect could have been detected with the available data on these more recent antidepressants 12.…”
Section: Introductionmentioning
confidence: 71%
“…41,52,69,83,86,111,119,122,128,133,135 Only five of these studies that used ultrasound to determine gestational age, 111,119,128,133,135 four of which reported odds ratios adjusted for confounding factors. These studies did not find an increased risk of an infant being small for gestational age (adjusted pooled OR of 1.04 , 95% CI, 0.64 to 1.69; I 2 =30%) with SSRI use during pregnancy.…”
Section: Infant/child Outcomes: Birth Parametersmentioning
confidence: 99%
“…42,45,49,53,64,90,111,112,122,128,133,146 Based on eleven observational studies, there is evidence of an increased risk of preterm birth (< 37 weeks gestation) and that the magnitude of risk may vary by timing of exposure, but current evidence is inadequate to establish reliable estimates. The most relevant of these studies is a medium risk of bias study that reported a statistically significant increased risk of preterm birth with SSRI use during pregnancy for any reason, compared with pregnant women with a documented psychiatric illness who did not receive an SSRI (or other antidepressant or antipsychotic drug) during pregnancy; adjusted OR 2.68 (95% CI, 1.83 to 3.93), 128 While this study did not limit the diagnoses to depression, gestational age was determined by ultrasound.…”
Section: Infant/child Outcomes: Birth Parametersmentioning
confidence: 99%
See 1 more Smart Citation